Effects of temperature on the metabolic stoichiometry of Arctic zooplankton - Alcaraz, M.; Almeda García, Rodrigo; Saiz, E.; Calbet, A.; Duarte, C. M.; Agustí, S.; Santiago, R.; Castro Alonso, Ayoze (Biogeosciences, 2013)
We assessed the relationship between zooplankton metabolism (respiration and inorganic N and P excretion) and "in situ" temperature through a grid of stations representing a range of natural temperature variation during the ATOS-Arctic cruise (July 2007). The objective was to explore not only the direct effects of temperature on zooplankton carbon respiratory losses (hereafter CR) and NH4-N and PO4-P excretion rates (hereafter NE and PE, respectively), but also to investigate whether these metabolic pathways responded similarly to temperature, and so how temperature could affect the stoichiometry of the metabolic products. Metabolic rates, normalised to per unit of zooplankton carbon biomass, increased with increasing temperature following the Arrhenius equation. However, the activation energy differed for the various metabolic processes considered. Respiration, CR, was the metabolic activity least affected by temperature, followed by NE and PE, and as a consequence the values of the CR : NE, CR : PE and NE : PE atomic quotients were inversely related to temperature. The effects of temperature on the stoichiometry of the excreted N and P products would contribute to modifying the nutrient pool available for phytoplankton and induce qualitative and quantitative shifts in the size, community structure and chemical composition of primary producers that could possibly translate to the whole Arctic marine food web. 697 689 9 2,468 3,753 Q1 Q1 SCIE